Clinical drug data (McGraw-Hill Education, 2010)
Handbook of Clinical Drug Data is the most comprehensive, well-referenced book available on the selection, use, and clinical aspects of virtually any drug. Compiled by expert clinicians, this quick-access guide delivers the data you need to prevent adverse drug reactions in your patients and help you select drugs for both general and special patient populations